Where Has the Time Gone? Addressing Collaboration Overload in a Networked Economy. (November 2013) - Cross, Rob; Gray, Peter
As a result of the spread of social media and collaboration technologies in the workplace, the adoption of matrix-based structures, and the proliferation of initiatives to create a "one firm" culture, many organizations are experiencing collaboration overload. Too often, excessive collaboration harms organizational performance, overworking employees for only marginal gains. High-performing employees are especially vulnerable because they already shoulder a disproportionate collaboration burden. This article shows how traditional approaches to improving collaboration often invisibly slow decision making and hurt performance, and describes how companies can identify and address points of collaboration overload and use structural and behavioral interventions to streamline information-sharing and decision-making interactions.